2009 International Conference on Mechatronics and Automation 2009
DOI: 10.1109/icma.2009.5246704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastic controlling parameters on the PCD burnishing system

Abstract: Burnishing processing is effective in leveling off the cutting marks on the machined surface of workpiece formed by pre-machining tools. The effect of elastic controlling parameters on burnishing force, surface roughness and microhardness of aluminum alloy workpiece burnished with elastic burnishing polycrystalline diamond (Pf.D) tools is studied experimentally with a theoretical analysis. The topics in choosing the optimum elastic controlling burnishing parameterspretightening force and rigidity coefficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was reported that in China the identified resources of oil shale is 3.15 billion tons, and the forecast resources 45.2 billion tons. Counted on the basis of six percent of oil content, the identified shale oil is 0.19 billion tons, and the forecast oil 2.71 billion tons [2]. Several countries, such as Estonia and Israel, have been being researched oil shale's composition, properties and applied technology widely and deep [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that in China the identified resources of oil shale is 3.15 billion tons, and the forecast resources 45.2 billion tons. Counted on the basis of six percent of oil content, the identified shale oil is 0.19 billion tons, and the forecast oil 2.71 billion tons [2]. Several countries, such as Estonia and Israel, have been being researched oil shale's composition, properties and applied technology widely and deep [3].…”
Section: Introductionmentioning
confidence: 99%